ZBTB7A as a novel vulnerability in neuroendocrine prostate cancer - Bae, Song Yi; Bergom, Hannah E.; Day, Abderrahman; Greene, Joseph T.; Sychev, Zoi E.; Larson, Gabrianne; Corey, Eva; Plymate, Stephen R.; Freedman, Tanya S.; Hwang, Justin H.; Drake, Justin M. (Frontiers in Endocrinology, 2023)
Neuroendocrine prostate cancer (NEPC) is a highly aggressive subtype of prostate cancer. NEPC is characterized by the loss of androgen receptor (AR) signaling and transdifferentiation toward small-cell neuroendocrine (SCN) phenotypes, which results in resistance to AR-targeted therapy. NEPC resembles other SCN carcinomas clinically, histologically and in gene alterations. Here, we leveraged SCN phenotype scores of various cancer cell lines and gene depletion screens from the Cancer Dependency Map (DepMap) to identify vulnerabilities in NEPC. We discovered ZBTB7A, a transcription factor, as a candidate promoting the progression of NEPC. Cancer cells with high SCN phenotype scores showed a strong dependency on RET kinase activity with a strong correlation between RET and ZBTB7A dependencies in these cells. Utilizing informatic modeling of whole transcriptome sequencing data from patient samples, we revealed distinct gene networking patterns of ZBTB7A in NEPC versus prostate adenocarcinoma. Specifically, we observed a robust association of ZBTB7A with genes promoting cell cycle progression, including apoptosis regulating genes. Silencing ZBTB7A in a NEPC cell line confirmed the dependency of cells on ZBTB7A for cell growth via suppression of the G1/S transition in the cell cycle and inducing apoptosis. Collectively, our results highlight the oncogenic function of ZBTB7A in NEPC and emphasizes the value of ZBTB7A as a promising therapeutic strategy for targeting NEPC tumors.